NARRATIVES IN THE DIGITAL AGE: ASSESSING THE IMPACT OF DIGITAL STORYTELLING AND SOCIAL MEDIA ON TOURISM DESTINATION BRANDING AND CONSUMER ENGAGEMENT - Zokirova, Vaziraxon ("Science Shine" International scientific journal, 2024)
Abstract: In the rapidly evolving digital landscape, storytelling has emerged as a pivotal tool in tourism marketing, enabling destinations to forge deeper connections with potential travelers. This paper delves into the transformative power of digital storytelling and its profound impact on tourism destination branding and consumer engagement through social media platforms. [1] By employing an integrative methodology that encompasses content analysis, consumer surveys, and case studies, this research aims to elucidate how digital narratives sculpt consumer perceptions and influence travel intentions. [2] The findings reveal that effective digital storytelling strategies, characterized by immersive multimedia elements and interactive engagement, significantly enhance destination branding and stimulate consumer interest. [3].This study contributes to the burgeoning discourse on digital marketing in tourism by offering actionable insights for practitioners and charting future research directions in an era where digital engagement is paramount.